2021
DOI: 10.24018/ejedu.2021.2.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Study of Teacher Education Graduates of the Eastern Visayas State University-Tanauan Campus, Philippines

Abstract: The study's purpose was to examine the employment characteristics of teacher education graduates from the classes of 2013 to 2017. Specifically, to explore a graduate's perception of the extent of the relevance of their chosen program curriculum learning areas to employment, and the extent of the use of competencies and values they learned at university. A survey study design that is descriptive was utilized in the study with a random sample of 179 graduates identified as the primary study respondents. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 0 publications
7
25
0
Order By: Relevance
“…2020) and Reusia et al (2020) reported that there are more employed than unemployed graduates. This finding also accords with Almejas et al (2017), Cañizares (2015), Cornillez et al (2021), Gines (2014), and Rojas and Rojas (2016), whose findings revealed that most teacher education graduates are permanent. This means that WPU-CED graduates are employable and that there is work available in the area.…”
Section: Training and Advanced Studies Attended After Collegesupporting
confidence: 91%
See 3 more Smart Citations
“…2020) and Reusia et al (2020) reported that there are more employed than unemployed graduates. This finding also accords with Almejas et al (2017), Cañizares (2015), Cornillez et al (2021), Gines (2014), and Rojas and Rojas (2016), whose findings revealed that most teacher education graduates are permanent. This means that WPU-CED graduates are employable and that there is work available in the area.…”
Section: Training and Advanced Studies Attended After Collegesupporting
confidence: 91%
“…Several teacher education institutions in the Philippines conducted Graduate Tracer Studies (GTS) to track and profile their Bachelor in Elementary Education (BEED) and Bachelor of Secondary Education (BSED) graduates (Abas et al, 2020;Abela et al, 2015;Aclan et al, 2018;Almejas et al, 2017;Antiojo, 2018;Aquino et al, 2015;Bihag-boholano, 2012;Caingcoy & Barroso, 2020;Cañizares, 2015;Cornillez et al, 2021;Daguplo et al, 2019;Gines, 2014;Oboza, 2017;Rojas & Rojas, 2016;Reusia et al, 2020;Tutor et al, 2019;Ulanday, 2021). Abas et al (2020) showed that the majority of the graduates are hired, notwithstanding the various competencies gained throughout their college years.…”
Section: Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alumni assess that the curriculum provided by the college is relevant and greatly contributes in supporting their work. Communication skills and self-confidence are considered the most supportive in the workplace (Cornillez et al, 2021). The majority of respondents had permanent or regular employment and worked locally within the region, according to the findings.…”
Section: Introductionmentioning
confidence: 83%